Β-Carotene Content and Quality Properties of Probiotic Yoghurt Supplemented with Podang Urang Mango Extract. Issue 1 (1st April 2022) - Afiyah, D N; Sarbini, R N; Suryati, T
Abstract: Nowadays, the consumption of probiotic yogurt has been a significant increase. Mostly people prefer to consume probiotic yoghurt because of its taste and high nutrients. However, in the manufacturing process of probiotic yogurt, a thermal process causes some nutritional losses, e.g., β-carotene. Therefore, to replace the loss of β-carotene during this thermal process, then added an extract of Podang Urang mango ( Mangifera indica L.). Podang Urang Mango is one of the famous fruits favored by consumers in Kediri, East Java. This fruit is available in a significant amount in Kediri, so the sustainability of the probiotic yogurt with the addition of Podang mango will be acceptable. This research objective was to determine the quality properties and β-carotene of the probiotic yogurt supplemented with Podang Urang mango extract. The probiotic yogurt was made by adding 3% (v/v) of starter culture ( Lactobacillus delbrueckii subsp bulgaricus RRAM-01 and Streptococcus salivarius subsp thermophilus RRAM-01 ) and Podang Urang Mango extract at 0%, 2%, 4%, 6%, 8%, and 10% (v/v) divided in four replications. pH, titratable acid, viscosity, and β- carotene content included as the observed variables. The results showed that Podang Urang mango extract had a significant effect on the quality properties, which could significantly lower the pH, increase the titratable acid, and increase the viscosity of probiotic yogurt. The thermal process of making probiotic yoghurt at 85-90°C for 35 minutes had lowered the amount of β-carotene. However, the supplementation of Podang Urang mango extract showed significantly increase the yogurt β-carotene. The increase of β-carotene could be influenced by the use of Podang Urang mango extract in yoghurt. The more Podang Urang mango extract added, the greater the β-carotene content found in yoghurt.